IMPROVED KNOWLEDGE OF YOUTH RELATED TO ANEMIA - Riesmiyatiningdyah Riesmiyatiningdyah; Kusuma Wijaya Ridi Putra; Agus Sulistyowati (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Health promotion activities about anemia in adolescents at the Islamic Boarding School of Tahfidz Putri Hidayatullah, Sidoarjo are a form of community service in the form of counseling aimed at increasing the knowledge of young women about anemia that often appears in adolescents. The activity will be held on March 28, 2021 at the Islamic Boarding School of Tahfidz Putri Hidayatullah, Sidoarjo. The target is young women who are female students at the Islamic Boarding School of Tahfidz Putri Hidayatullah, Sidoarjo. Prior to the implementation of these activities, there is a process of preparing activities for approximately 3 weeks before the activities are carried out, starting from determining the theme of the extension to applying for permits to the relevant parties. As a form of evaluation, the activity was attended by 24 female students and 1 boarding teacher/caregiver, the participants participated in the activity happily and looked very enthusiastic, health promotion activities could run on time and smoothly.